Factors affecting well-being in brain tumor patients: An LMIC perspective - Shah, Nasim Zahid; Masroor, Taleaa; Zahid, Nida; Zahid, Wajeeha; Hassan, Aneesa; Azam, Iqbal; Ahmad, Khabir; Bhamani, Shireen Shehzad; Jabbar, Adnan Abdul; Asad, Nargis; Shamim, Muhammad Shahzad; Khan, Rashid Jooma; et al. (Frontiers in Psychology, 2023)
Introduction Brain tumor is a devastating and often fatal diagnosis; quality of life and patient well-being are important goals of treatment. This study addresses the gap in culture-specific literature exploring the needs and coping strategies of brain tumor patients within an LMIC setting. Methodology A qualitative approach was undertaken using an exploratory descriptive study design. In-depth interviews were conducted to capture the perspective of 250 brain tumor patients at a private tertiary center followed by extensive content analysis to identify major themes and sub-themes across responses. Results The analysis identified three major themes: (i) Factors affecting the lives of brain tumor survivors (BTSs) and their impact (ii) What works to improve QoL according to the survivors’ perspectives, and (iii) Coping tactics & fostering healthy relationships. The need for financial navigation strategies improved patient-physician relationships, and reinforcing positive coping strategies were emphasized. Conclusion In our population, family support and spiritual connection played an important role in helping patients mitigate the psychosocial burden of illness. However, financial concerns were pervasive and need to be addressed for better overall well-being.